Suitability for farmer-led solar irrigation development in Mali - International Water Management Institute (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Approximately 72% of Mali’s population is engaged in farming and agriculture is a major economic sector (FAO 2017a). Agriculture is predominantly rain-fed and hence vulnerable to variability in rainfall. Crop yields are affected by dry spells and droughts leading to loss of income and food insecurity. According to the Food and Agriculture Organization of the United Nations (FAO), only 5.3% of the agricultural area was under irrigation in 2011 (FAO 2016). Investments in motorized water pumps to irrigate fields could benefit 4.7 million farmers and generate net revenues up to USD 39 million per year (Agwater Solutions Project 2012). As the price of solar photovoltaic panels is decreasing rapidly, solar water pumps are becoming an affordable, climate-smart solution for small-scale farmers across Mali.